Development of a systems based modular approach to link complex diseases - Rende, Deniz. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
A novel systems based modular approach was developed in this study to investigate the shared underlying mechanisms of three prevalent complex disorders: cardiovascular disease (CVD), Type 2 diabetes (T2D) and Alzheimer‘s disease (AD). The disease related functional linkage networks were constructed and analyzed in every aspects of modularization. The fundamental biological processes were deciphered through integration of various levels of "omics" data. The identification of the links between these diseases was accomplished through the shared proteins and biological processes. The cardiovascular disease functional linkage network (CFN) containing 1536 proteins and 3345 linkages was constructed using proteins encoded by 234 genes associated with cardiovascular disease. The modular architecture of this network and its integration with "bibliomics" indicated that blood coagulation, lipid metabolism and renin-angiotensin systems were found to be linked to CVD as expected. The modularization in CFN was anticipated to exert a potential to develop a general perspective, hence the functional modules enumerated from CFN were evaluated in terms of shared pathways, co-localization, co-expression and associations with diseases. The members of the top scoring functional modules were assembled in a condensed network representing the fundamental biological processes. The approach was later applied to the other two complex disorders. The functional linkage networks include 2734 proteins / 14823 linkages (TDFN) and 1587 proteins / 7785 linkages (ADFN) for Type 2 diabetes and Alzheimer‘s disease, respectively. The individual fundamental processes and signalling cascades observed in each of these diseases are converged at blood coagulation, glucose homeostasis, lipid metabolism, oxidative stress and inflammation. The central roles of the proteins generating inflammatory response in all disease networks indicate that inflammation might be the missing link between CVD, T2D and AD.
Keywords: Genetic disorders.; Cardiovascular system -- Diseases.; Non-insulin-dependent diabetes.; Alzheimer's disease.; Linkage (Genetics)